Integration : A New Approach to Youth Employment Programs - Datta, Namita; Assy, Angela Elzir; Buba, Johanne; Watson, Samantha (Washington, DC: World Bank, 2019)
This guide aims to provide general guidance to project managers and project teams on the design and implementation of integrated, cross-sectoral youth employment programs.The aim of the integrated programs described in this guide is to bring together supply- and demand side interventions to simultaneously address three interrelated objectives:Promote job creation for the target population; Improve the quality of jobs young people already have, many of which are in the informal sector; and Help prepare young job seekers for jobs or to move from low- to higher-quality jobs.This guide has been developed by a team drawn from multiple World Bank Global Practices and is based on evidence, experience, and lessons learned from a variety of sources.This guide attempts to present a broad framework to help project teams explicitly link supply- and demand-side considerations in the context of an integrated youth operation: Section one briefly introduces the conceptual framework guiding project design, the type of diagnostic work needed, and the diagnostic models and tools that can be used. Some of these tools are generic, but can be adapted to look more deeply at youth employment issues; Section two discusses how teams could improve the design of supply-side interventions. Reviews of successful youth employment programs suggest they have certain characteristics in common: they offer a diversified package of interventions that address the constraints of a heterogeneous group of beneficiaries; include good identification, profiling, and follow-up systems; and rely on appropriate contracting and payment systems for providers and strong engagement with the private sector; Section three presents practical suggestions to improve the design of a youth employment program on the demand side. The evidence on what works in fostering more and better job creation at the firm level is not as robust as for the supply side. Nonetheless, there are interventions that can be adapted to stimulate job creation and/or labor productivity growth at the firm level with a focus on youth.; Section four describes how teams might develop a fully integrated program/project. In most cases, project managers might need to begin with designing either a supply- or demand-side intervention and then try to integrate or connect it with one or more interventions aimed from the other side. In other cases, the project team may be able to design a fully integrated program from the start. Such integrated approaches are new and require systematic testing, experimentation, and piloting to fine-tune design elements. The guide is supplemented by ten annexes which summarize useful tools and techniques that can be adapted to the youth employment context.